Enhancing Foreign Language Teachers’ Professional Competence Through Lesson Study - Wahdah, Nurul; Nirwanto, Rahmadi; Dewi, Amalia Permata (Langkawi: Journal of The Association for Arabic and English, 2025)
Although research on lesson study and teacher professional development has been extensively documented, scholarship addressing these issues in remote and underdeveloped contexts particularly Central Kalimantan remains relatively limited. To address this gap, the present study seeks to enhance the professional competence of foreign language teachers in developing Merdeka Curriculum teaching modules through the systematic implementation of Lesson Study. This study was conducted over a four-month period (May–October 2023) employing observation and documentation techniques for data collection. Within the observation phase, the study adopted a three-cycle Plan–Do–See structure, which comprised activities such as learning outcome analysis, formulation of learning objectives, development of teaching modules, and preparation of modules for the Project for Strengthening the Profile of Pancasila Students and the Profile of Rahmatan lil Alamin Students (P5PPRA). Each cycle involved collaborative planning, implementation, and reflection between the researchers and the participating teachers. The findings demonstrate significant improvements in teacher engagement and curriculum understanding. Observational data indicated a performance category enhancement from "good" to "excellent," with average performance scores increasing from 3.2 in the first cycle to 3.6 in the third cycle. Through Lesson Study (LS), teachers are able to develop teaching modules and adopt new pedagogies through in-depth collaborative discussions and active involvement in each stage of the cycle so that they are able to accelerate with new  government policies. This study provides practical insights for improving educational quality in remote areas and establishes a foundation for developing more contextual education policies in Indonesia.